Business ecosystems - Reeves, Martin; Pidun, Ulrich (Inspiring the next game : strategy ideas for forward looking leaders, 2022)
A business ecosystem may be defined as a dynamic group of largely independent economic players that create products or services that together constitute a coherent solution for customers. Business ecosystems are high on the agenda of many business leaders. They are now highly prevalent, frequently disruptive, and all companies should add the required capabilities to their strategy toolbox. Business Ecosystems is based on more than three years of research by the BCG Henderson Institute, their work with dozens of companies on their ecosystem strategies, and hundreds of conversations with academics, managers, investors, entrepreneurs, and government employees. Part I reviews the fundamentals of business ecosystems - definition, design, success factors, governance, strategies. Part II elaborates on special topics, such as trust and data, industry applications, and their potential for sustainability. Ecosystems might not be a solution for all problems, but they are also not a transitory phenomenon. The field is evolving fast and as the success factors for creating, managing and participating in business ecosystems are increasingly accepted and understood, many established and emerging companies have the opportunity to put themselves in a position to unlock great innovation and value creation potential by engaging in ecosystem business models. This book will support business professionals and executives on this journey.